Representasi Body Positivity para Liyan pada Instagram “Inspirasien” - Okta Annisa Kusumawardhani (Jurnal Ilmu Komunikasi, 2022)
Liyan are a group of people who are considered a minority or can be marginalized. People with chronic diseases are one of the others that are rarely represented in the media. The media has always featured people who are physically perfect and flawless, and there is no element of inclusiveness on the part of chronic disease survivors. With the presence of social media, various accounts began to appear that spread the concept of body positivity. This study uses a qualitative descriptive method to analyze and carry out elaboration and uses the lens of a critical paradigm and uses Roland Barthes' semiotic analysis technique which analyzes texts from the meaning of connotations, denotations, and accompanying myths. The results of the study show that the concept of body positivity has been shown in Instagram account posts as a true form of representation of chronic disease survivors. The concept of body positivity is reflected in Inspirational posts that have a positive body image.